씨프로후록싸신 - 메티실린 내성 황색 포도구균에 의한가토 각막염 모델에서 점안 항생제의 항균효과 비교 - 김익수; Ik Soo Kim; 신은미; Yeun Mi Shin; 김수진; Soo Jin Kim; 차홍원; Hung Won Tchah; 한영호; Young Ho Hahn; 한태원; Tae Won Hahn (Daihan angwa haghoi jabji, 2000)
저자들은 세균성 각막염 환자로부터 검출된 씨프로후록싸신과 메티실린에 내성을 보이는 황색 포도구균에 대해 실험실적 항생제 감수성 검사를 시행하고 본 균주에 의한 가토 각막염 모델을 이용하여 4가지 점안 항생제의 항균 효과를 평가하였다. 씨프로후록싸신-메티실린 저항성 포도구균 100CFUs/10㎕를 백색 가토의 각막 실질내로 주사하여 각막염을 유발시켰다.30마리의 가토 3 0안을 무작위로 5군으로 분류한 후, 0.3% 씨프로후록싸신, 0.3% 트로바후록싸신, 5% 반코마이신, 5%세파졸린, 그리고 멸균 증류수를 15분 간격으로 6시간 동안 각각 25방울(750㎕)을 점안하였다. 마지막 점안제 투여 1시간 후에 마취제를 이용하여 가토를 도살하고 각막을 절제하여 조직분쇄기로 갈아 희석후 혈액배지에 분주하였다. 배양 4 8시간에 각각의 각막내 세균의 수를 colony forming unit 단위로 측정하였다. 각막 절제전 전방수를 추출하여 약물 농도를 측정하였다. 반코마이신 점안군(n=6)에서 세균 군락 수(lo g10값, 평균±표준오차)는 4.8 5±0.64, 씨프로후록싸신 점안군은 6 .16±0.46, 트로바후록싸신 점안군은 6.58±0.29, 세파졸린 점안군은 6.25±0.25이었고, 대조군인 멸균 증류수 점안군은 6.57±0.33로 나타나 반코마이신 점안군만이 다른 점안군과 비교하여 통계적으로 유의한 항균 효과를 나타내었다(P＜0.05). 그러나 4가지 항생제 모두 6시간의 단기 치료로는 각막내 세균을 완전히 멸균하지 못하였다. 결론적으로, 씨프로후록싸신-메티실린 내성 황색 포도구균에 의한 각막염의 치료에 있어 임상적으로 상용되는 항생제 및 종류가 서로 다른 후루오로퀴놀론 제재의 사용은 무의미하고 반코마 이신의 투여가 가장 효과적이었다(한안지 41:807~814, 2000). To compare the antimicrobial efficacy of several antibiotics in the treatment of ciprofloxacin and methicillin-resistant staphylococcus aureus(MCRSA)keratitis, we established a rabbit keratitis model by using MCRSA isolated from keratitis patient. A strain of MCRSA, approroximately 100 colony forming units in 10㎕of phosphate buffered saline was injected intrastromally into the each cornea of New Zealand white rabbits. 30 rabbtits(30 eyes)were randomly divided into 5 groups and treated with either 0.3% ciprofloxacin, 0.3% trovafloxacin, 5% vancomycin, 5% cefazolin, or sterile deionized water. Topical antibiotics were administered every 15 min for 6 hours(750 ㎕). Rabbits were sacrified 1hour after the last eyedrop, and excised corneas were homogenized, diluted, and plated on BAP medium. Bacterial colonyforming units per cornea were quantified after 48-hour incubation. Aqueous humor were collected from each eye and drug concentration was counted with HPLC. The log1 0 value of colony forming units(CFUs)of vancomycin treated group was 4.85±0.64; ciprofloxacin, 6.16 ±0.46; trovafloxacin, 6.58 ±0.29; cefazolin, 6.25±0.25;and sterile deionized water, 6.57 ±0.33. In view of mean CFU, vancomycin showed greater antimicrobial activity and it was statistically significant(p＜0.05). However, all of these treatment did not completely sterilize any corneas with 6-hour treatment. From these results, only topical vancomycin(5%) represented effective antimicrobial activity with short-term treatment in rabbit keratitis with MCRSA(J Korean Ophthalmol Soc 41:807~814, 2000).